The Impact of Investor Sentiment on Value and Growth Stocks Return - Suchi Gamella Putri; Tafdil Husni; Rida Rahim (CV. Lenggogeni Data Publishing, 2023)
The aim of this research is to investigate the impact of investor sentiment on value and stocks return. Two investor sentiment indicators, volatility index VIX and sentiment index are used as independent variables. Technical proxies (relative strength index, psychological line index, trading volumes and adjusted turnover rate) are used to construct sentiment index using principal component analysis. The dependent variable is value and growth stocks return formed based on the book to market ratio. Three Fama-French factors are used as control variables to isolate the impact of investor sentiment from systematic risk and fundamental factors. We use companies listed on Kompas 100 index over the sample period February 2017-January 2023. The sampling technique was carried out by purposive sampling and obtained 45 companies as the research samples. The empirical analysis employs multiple regression analysis using 1.385 daily time series computed by Microsoft Excel and Stata 13. The regression results indicate that volatility index VIX has a negative significant effect on value and growth stocks return. Sentiment index has a positive and significant effect on value stocks return but does not have a significant effect on growth stocks return. Investor sentiment has a greater effect on value stocks than growth stocks.